Teologi Agama-agama dalam Lensa Hospitalitas Pentakostal - Anggi Maringan Hasiholan; Joshua Alvis Stevenson (Sekolah Tinggi Theologia Nazarene Indonesia, 2023)
The multi-religious reality in Indonesia is a necessity. Religion has the highest value in the social life of people in Indonesia. Therefore, religion is used as a source of inspiration that regulates the survival of interfaith life. However, differences in religion can be a source of problems if they are not able to be managed properly. Conflicts and violence on behalf of religious defenders are prevalent in Indonesian society. The Holy Spirit that dwells in Pentecostal believers should bring hospitality in society. Therefore, a systematic construction of the position and relationship of Pentecostal hospitality with the theology of religions is needed. The research method used is descriptive-intrepretative qualitative and the analysis uses comparative and argumentative approaches. The results show that Pentecostal Hospitality brings grace to society at large. The Holy Spirit is the one who enables Pentecostals to do comparative and pericoretic theology in relation to religions.